COMMUNITY ASSISTANCE IN CONSTRUCTING A CLEAN WATER INSTALLATION AT THE BONGGO HEALTH CENTER, ARMOPA VILLAGE, BONGGO DISTRICT, SARMI REGENCY - Joni, Joni; Siregar, Samuel Parlindungan; Ranteallo, Obet Takke; Palamba, Pither; Tosuli, Yohanis Tangke; Rantepulung, Selyus; Giai, Agustinus; Werdhani, Anastasia Sri; Tambing, Enos; Kaiway, Mickael Ruben; Kati, Oktavianus; Kariongan, Yakobus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Access to clean water is a fundamental necessity that underpins effective public health services and the operational efficiency of health facilities, including the Bonggo Health Center in Sarmi Regency. Recognizing the importance of reliable clean water access, a community assistance initiative was launched to establish a sustainable water installation system at the Bonggo Health Center. This initiative is crucial to enhancing the health center’s ability to deliver quality healthcare services, as safe, clean water is essential for various healthcare functions, from sanitation to patient care. The primary aim of the assistance program is to equip the Bonggo Health Center with a dependable source of clean water, ensuring it meets health and safety standards for use in medical services. To achieve this goal, the implementation method was carefully structured, involving several sequential steps. First, the service team conducted a comprehensive location survey to assess the water requirements and potential challenges. Following this, the team engaged in in-depth problem discussions, planning sessions, and preparatory work to lay the groundwork for the installation. The actual construction of the water installation was then carried out, followed by rigorous testing and evaluation to ensure functionality and quality. Through close collaboration with the Armopa Village community, the service team successfully completed a fully operational clean water installation. This unit now provides a reliable supply of high-quality water for the Bonggo Health Center, significantly improving the center’s capacity to serve the healthcare needs of the surrounding community. This installation not only meets immediate needs but also sets a foundation for sustained health service enhancements and community well-being in the region.